My penguin Osbert - Kimmel, Elizabeth Cody.; Lewis, H. B. (Cambridge, Mass. : Candlewick Press, 2004)
When a boy finally gets exactly what he wants from Santa, he learns that owning a real penguin may not have been a good idea after all.
4.2
K-3
Keywords: Penguins -- Juvenile fiction; Gifts -- Juvenile fiction; Christmas -- Juvenile fiction; Penguins -- Fiction; Gifts -- Fiction; Christmas -- Fiction; Penguins -- Fiction; Gifts -- Fiction; Christmas -- Fiction